Pengaruh Pupuk N, P, K dan Mg terhadap Pertumbuhan dan Kualitas Lidah Buaya (Aloe vera chinensis) pada Lahan Gambut Indragiri Hilir Riau - Catur Wasonowati; - Sudrajat; Sudirman Yahya (Universitas Trunojoyo Madura, 2008)
The objective of this research was to study the effect of N, P, K and Mg fertilizers on growth and quality of Aloe vera chinensis in peat soil of Indragiri Hilir Riau. The research was conducted at PT Bhumireksa Nusasejati Plantation, Indragiri Hilir Riau. The research was arranged by Factorial Randomized Block Design with 4 factors, 4 levels, 3 replications. The first factor was N dosage fertilizer (N0 is equal to 0g, N1 is equal to 5g, N2 is equal to 10g, N3 is equal to 20g N/plant/month), The second factor was P dosage fertilizer (P0 is equal to 0g, P1 is equal to 4g, P2 is equal to 8g, P3 is equal to 16g P2O5/plant/month), The third factor was K dosage fertilizer (K0 is equal to 0g, K1 is equal to 7.5g, K2 is equal to 15g, K3 is equal to 30g K2O/plant/month), The fourth factor was Mg dosage fertilizer (Mg0 is equal to 0g, Mg1 is equal to 2.5g, Mg2 is equal to 5g, Mg3 is equal to 10g MgO/plant/month). The results showed that the application of N, K and Mg dosage significantly increased plant height, leaf length, leaf width, leaf thickness, and the number of leaf by quadratic response. Combination of N and P fertilizer significantly raised the leaf fresh weight. The complete treatment (NPKMg) and single factor either N and Mg did not increase the total chlorophyll and protein content , in contrast, P and K as a single factor significantly increased the total chlorophyll but not protein content. Gel of Aloe vera consisted of 17 essential amino acids